2007
DOI: 10.2307/25065861
|View full text |Cite
|
Sign up to set email alerts
|

Metteniusaceae, an early‐diverging family in the lamiid clade

Abstract: A phylogenetic analysis based on a combined dataset of three genes, nuclear 18S rDNA and plastid rbcL and atpB, indicates that the enigmatic Neotropical genus Metteniusa is a member of the lamiid (euasterid I) clade. The genus appears as an isolated taxon near, but perhaps not related exclusively to, Oncothecaceae, which supports its recognition as a separate family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 29 publications
2
31
1
Order By: Relevance
“…Drosera, Rivadavia et al 2003). Consistent with the west wind drift, longdistance dispersal appears to be more common from Australia to New Zealand Wagstaff and Wege 2002;Ford et al 2007), although there have been a few well supported cases of dispersals in the other direction (Wagstaff and GarnockJones 2000;Lockhart et al 2001;Wanntorp and Wanntorp 2003;Meudt and Bayly 2008).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Drosera, Rivadavia et al 2003). Consistent with the west wind drift, longdistance dispersal appears to be more common from Australia to New Zealand Wagstaff and Wege 2002;Ford et al 2007), although there have been a few well supported cases of dispersals in the other direction (Wagstaff and GarnockJones 2000;Lockhart et al 2001;Wanntorp and Wanntorp 2003;Meudt and Bayly 2008).…”
Section: Introductionmentioning
confidence: 89%
“…Many phylogenetic studies have found that several Australian and New Zealand groups have closely related species or species complexes, suggesting recent or frequent dispersal or both (Breitwieser et al 1999;von Hagen and Kadereit 2001;Smissen et al 2003;Meudt and Simpson 2006;Ford et al 2007;. Groups with dispersible propagules might have repeatedly crossed the Tasman Sea (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, P. radicatum occurs in the Tasmanian mountains and is considered to have dispersed there and diverged contemporaneously with the radiation of Pachycladon in New Zealand [21,22]. Other taxa are also shared between the two countries, but these are considered to have dispersed eastward from Australia to New Zealand and include, for example, Craspedia [66], Montigena [67], Poranthera [68], Scleranthus [69], and Stylidiaceae [70]. This pattern of eastward dispersal means it is plausible that Pachycladon could have originated in Australia and then subsequently dispersed to New Zealand.…”
Section: Discussionmentioning
confidence: 99%
“…Wagstaff & Garnock-Jones 1998;Lockhart et al 2001;Smissen et al 2003;Meudt & Simpson 2007) and to help bring more precision to the systematics of many New Zealand plant groups (e.g. Heenan et al 2002;Glenny 2004;Smissen et al 2004;Perrie & Brownsey 2005;Ford et alPlantago (Plantaginaceae) is a large genus of wind-pollinated plants, with over 200 species distributed worldwide. Eight species native to New Zealand were recognized in the most recent taxonomic treatment (Sykes 1988a) ( Table 1).…”
Section: Introductionmentioning
confidence: 99%